Spatial non-stationary movement of a marine tethered system at maneuvering - Trunin, K. S. (My University, 2017)
When designing an underwater towed system (UTS) and selecting possible modes of its movement, of great importance is calculation of the parameters of the towed system (TS) movement at carrier vessel maneuvering. This is caused by the fact that the TS changes its running depth when the vessel moves with an alternating speed, which leads to the appearance of a considerable number of dynamic components of the tether tension and unstable modes of the TS movement.
Trunin, K. S. Spatial non-stationary movement of a marine tethered system at maneuvering / K. S. Trunin // Shipbuilding & Marine Infrastructure. – 2017. – № 2 (8). – P. 103–114.
Keywords: marine tethered system (MTS); flexible connection (FC); underwater towed system (UTS); spatial non-stationary movement; mode of movement; circulation